Criminal Liability in Withdrawing Fiduciary Collateral to Leasing Parties by Debt Collectors Based on Law Number 42 Year 1999 on Fiduciary Guarantee - Aryono Aryono; Rina Arum Prastyanti* (Universitas Syiah Kuala, 2023)
This journal will discuss the criminal obligation of the leasing participation in withdrawing fiduciary collateral through current and future debt collectors in line with law number 42 of 1999 regarding Fiduciary guarantees. Leasing participation on Withdrawal of Fiduciary Collateral through Debt collectors according with the regulation. Efforts for criminal liability of the leasing participation within the revocation of fiduciary ensures through the gathering authority according with law number 42 concerning fiduciary collateral, indicating that a person who has a strength of attorney from a financial organization to a 3rd part for fiduciary ensures A guarantee penalty has in no way been held criminally responsible, it should be based on for that reason this series of actions, the person who offers the power of legal professional to withdraw from the fiduciary assure can satisfy the necessities inside the article of the criminal Code.